Company Involvement In Eradicating Criminal - Bayu Ramadhan Effendi; Ellydar Chaidir; M. Musa (International Conference On Law And Social Sciences, 2024)
Effective law enforcement can create a safer and more peaceful community environment. The existence of social welfare also has a positive impact on preventing criminal acts in society. Through this approach, it is hoped to reduce crime rates and strengthen social ties between individuals. Companies often become agents of change that positively contribute to society through welfare programs and corporate social responsibility activities. Companies can participate in efforts to prevent criminal acts and create order by paying attention to these aspects. The company is committed to supporting more inclusive and sustainable social development through various initiatives. The role of companies in improving society's welfare is believed to be a solution to eradicating criminal acts based on poverty. The first step that companies can take is to provide employment opportunities for the community and equal opportunities to develop. In addition, implementing corporate social responsibility programs will help improve the welfare of the surrounding community. Becoming a partner in sustainable development with the government and related institutions is also a way for companies to participate in creating a safe and prosperous environment for all parties involved.